Some remarks on the lithic assemblage from a coastal Ubaid-related settlement site on Delma Island, Abu Dhabi emirate, United Arab Emirates - Kallweit, Heiko; Beech, Mark Jonathan (Proceedings of the Seminar for Arabian Studies, 2020)
The Neolithic Ubaid-related settlement site on Dalma island was first discovered in 1992 by the Abu Dhabi Islands Archaeological Survey (ADIAS). Ubaid pottery sherds, lithics, marine shells, and fish bones were observed on the ground surface within the walled compound of the former Women’s Association, as well as external to the compound within the traffic island located on its northern side. Excavations subsequently took place directed by ADIAS team members, Elizabeth Shepherd-Popescu and Katelin Flavin (1994–1995), and by Mark J. Beech and Joseph Elders (1998). Excavations were renewed by the Abu Dhabi Tourism and Culture Authority (TCA Abu Dhabi) directed by Mark J. Beech (2014–2016). These excavations revealed that the settlement had up to 1.7 m of stratigraphic deposits below the modern-day ground surface. Traces of circular house structures were identified in the form of post-holes. Radiocarbon dating demonstrates that the site was occupied from the late sixth to the mid-fifth millennium BC. To date a total of more than 35,000 lithics have been retrieved from the site. During fieldwork carried out in 1998, Mark J. Beech and Jakub Czastka from the ADIAS team discovered that there was a raw flint source on the north-west coast of Delma Island. Unfortunately, this particular outcrop is no longer accessible due to subsequent construction activities, although some samples of the flint were collected from it. It is pale grey-brown to pale blue in colour with small sparkly inclusions and a thick bright white coloured cortex. Analysis of the lithic assemblage from the excavations suggests that the vast majority of final tools and even the management of rejects and production waste are believed to be of local origin. Only an extremely small number of imported final products were noted. The assemblage is marked by a low variety of tool types, with an emphasis on attrition tools in the form of wedges. Drills and perforating tools are common but less frequent. There was a limited quantity of arrowheads and large projectile points.